Gambaran Kompetensi Pedagogik Guru Ekonomi Kota Padang - Oknaryana Oknaryana; Jean Elikal Marna; Yolandafitri Zulvia (Universitas Negeri Padang, 2019)
This study aims to identify the pedagogical competence of teachers who are members of MGMP Economics in Padang City. This type of research is a quantitative descriptive. In collecting data, researchers distributed questionnaires to 32 teachers who were members of the MGMP of the Padang City Economics teacher. The results of this study indicate the average teacher's understanding of students in both categories with a mean of 2.84. Indicators of designing/planning learning are also in a good category with an average of 2.94. The indicators in implementing learning in the category are very good with an average of 3.28. The evaluation indicators of learning outcomes are in the good category with a good average and the last indicator for the development of students is in the good category with an average of 3.14. The average pedagogical ability of MGMP Teachers in Economics in Padang City is in a good category.